A sustainable consumers' consumption in the context of Arctic circular economy. Issue 1 (September 2020) - Karpova, S V; Cherenkov, V I; Cherenkova, N I
Abstract: The concept of circular economy has factually become a cornerstone for describing a necessary redesign of a hypothetic Arctic industrial eco-system or geosocioeconomic (GSE) system to get to a better sustainability. Given the quarter-century-old post-Soviet hibernation of Russian Arctic politics, the authors have largely focused their research on an analysis of relevant foreign sources. These sources were grouped by the following topics: (1) a model of the circular economy as the most suitable for such a remote and vulnerable region as the Arctic; (2) modifying the model of consumers' consumption taking into account the main principles of circular economy; and (3) creating a mental sustainability construct in the mind of sustainability stakeholders with emphasis on current and future students. Despite the fact that consumers' consumption holds a prominent role on the way toward the sustainable development of Arctic regions the said role is not well accounted for in the literature on circular economy. This paper contains the appeal to continue studying thoroughly the relationship between consumers' consumption and building a circular economy in the light of implementing the concept of sustainable development, which is especially important for the Arctic. The paper is supplied with graphic materials that could have a didactic value.